The Influence of Cyberloafing and Organizational Commitment to Employee Performance With Self-Control As A Moderation Variable - Ginna Novarianti Dwi Putri Pramesti; Widya Widya; Siti Ainul Kholipah; Mar’atus Solikhah; Lutfiyatut Tamamiyah (Publikasi Indonesia, 2024)
This research aims to investigate the impact of cyberloafing and organisational commitment on the performance of employees in the Department of Housing, Settlement Areas, and Land Affairs of Kuningan District (Dinas et al.), as well as to gain an understanding of the moderating influence of self-control in the relationship between cyberloafing and organisational commitment on employee performance. This research is motivated by frequent cases where employees engage in cyberloafing, negatively affecting their performance. The method used in this research is a descriptive quantitative method, utilising a questionnaire as a data collection tool. Using the random sampling method, the research sample consists of 70 randomly selected department employees. The SPSS program is used to analyse the data in this research. The research results indicate a negative and significant influence between cyberloafing and employee performance, while organisational commitment positively influences employee performance. Additionally, the test of the interaction of self-control as a moderator in the relationship between cyberloafing and organisational commitment on employee performance shows that self-control weakens the influence of cyberloafing on employee performance. In conclusion, individuals with high levels of self-control can reduce potentially harmful negative actions.